System inflammation role in cardiovascular and obstetric pathology - M. B. Igitova; E. V. Wobieva; E. V. Osipova; N. P. Gol’tsova (Кардиоваскулярная терапия и профилактика, 2009)
Recently, the role of inflammatory component in cardiovascular disease (CVD) pathogenesis has been widely accepted, and traditional CVD risk factors (RFs) were supplemented by the evidence on pro-inflammatory mediators’ role in atherosclerosis pathogenesis. At the same time, there is an overlap between chnical RFs of atherosclerosis and typical obstetric complications — gestoses and chronic placental insufficiency. Highly informative predictor of atherosclerotic complications is a marker of intravascular inflammation — highly sensitive C-reactive protein (hsCRP). The studies on hsCRP in obstetric complications are scarce and contradictory, and at the moment, there is no clear hypothesis of systemic inflammation role in pregnancy physiology and pathology.